Effects of three weeks of oxygen supplementation on oxygen saturation and recovery parameters of elite wrestlers - Demirhan, B. (Archives of biological sciences, 2014)
The purpose of this study was to investigate the effects of three weeks of oxygen supplementation on oxygen saturation, lactate level, and heart rate (HR) responses of elite wrestlers. The subjects included fourteen elite male wrestlers, mean age of the experimental group was 19.87±0.35; the mean age of the control group was 19.62±0.51. Both groups had similar height, weight and fitness parameters. Before and after training, the heart rates, lactate levels and oxygen saturation values were recorded. Consistent with our hypothesis, the oxygen saturation (SpO2) values of the experimental group increased significantly (p<0.05) while lactate and heart rate values decreased significantly. When the pre-exercise levels of oxygen saturation were compared, the oxygen supplementation group displayed significant differences in the 2nd and 3rd weeks (P<0.05). Pre-training HR and lactate levels in the three weeks did not differ significantly. The experiment group had higher measured SpO2 values immediately after exercise in the 3rd week (P<0.05); HR and lactate levels declined after oxygen supplementation (P<0.05). Only in the 2nd and 3rd week, the HR values were lower in favor of the experimental group (P<0.05). Our findings indicate that oxygen supplementation does not have a chronic effect in increasing oxygen saturation and reducing HR and lactate values; however, oxygen saturation was found to be effective during the short-term recovery periods.